2009
DOI: 10.1097/ico.0b013e3181967082
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Changes in Corneal Biomechanical Properties After Photorefractive Keratectomy and Laser In Situ Keratomileusis

Abstract: Both PRK and LASIK can affect the biomechanical strength of the cornea depending on the amount of myopic correction. The amount of biomechanical changes is larger after LASIK than after PRK. From a biomechanical viewpoint, PRK may be a less invasive surgical approach for the correction of myopia than LASIK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
3
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 43 publications
1
53
3
7
Order By: Relevance
“…Previous investigators took two readings (16)(17) , three readings (18)(19) , Table 3 Pairwise comparison of ROC curve Table 2 Data summary from receiver operating characteristic curves of pentacam parameters in normal and keratoconic eyes and four readings (20)(21)(22)(23) in their experimental protocols. Is it worth use the average of two, three or four consecutive measurements if you can be used to measure the best score?…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigators took two readings (16)(17) , three readings (18)(19) , Table 3 Pairwise comparison of ROC curve Table 2 Data summary from receiver operating characteristic curves of pentacam parameters in normal and keratoconic eyes and four readings (20)(21)(22)(23) in their experimental protocols. Is it worth use the average of two, three or four consecutive measurements if you can be used to measure the best score?…”
Section: Discussionmentioning
confidence: 99%
“…28 The observation of the reduction in CH and CRF values after LASIK and surface ablation procedures have also been demonstrated. [29][30][31][32] The same authors who concluded that the Corvis ST may not be reliable to quantify the effect of CXL in KC eyes have published another study where they showed that it was possible to evaluate the corneal biomechanical properties after LASIK, ReLEx flex, and ReLEx smile. 33 If the changes induced by CXL on parameters, such as CH and CRF are too subtle to be documented unlike those in the abovementioned clinical situations, then would it not be logical to conclude that the effect of CXL on corneal biomechanics may be too modest to be clinically relevant?…”
Section: How Then Can We Explain the Lack Of Clearly Documented Biomementioning
confidence: 99%
“…Studies have shown a greater decrease in both CH and CRF in LASIK eyes when compared with photorefractive keratectomy. 21 Thus patients with weaker biomechanics are more suitable for surface ablation with or without simultaneous crosslinking as compared to LASIK. Also, studies comparing SMILE and LASIK have found more reduction in biomechanics in patients that underwent LASIK, suggesting that the former may be more suitable for patients with pre-existing weaker biomechanics ( Figure 5).…”
Section: ) Refractive Surgerymentioning
confidence: 99%